2020
DOI: 10.1038/s41551-020-0563-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic tuning of protein–antigen fusions enhances the immunogenicity of T-cell vaccines

Abstract: Recent advances in immuno-oncology have generated renewed optimism for therapeutic antitumor vaccination, and peptide vaccines in particular are being extensively employed in clinical studies. However, peptide vaccines generally suffer from poor immunogenicity. Here, we pharmacokinetically tune vaccine responses via fusion of peptide epitopes to carrier proteins to optimize vaccine potency. Antigen-carrier fusions enable three factors to be simultaneously *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 64 publications
(144 reference statements)
0
39
0
Order By: Relevance
“…Albumin-binding dyes target draining lymph nodes and thus provide a strategy for the visual identification of sentinel lymph nodes following intratumoural administration 183 . Molecular vaccine cargo can also be designed to ‘hitch-hike’ albumin for the passive targeting of lymph node-resident APCs 173 , 184 . This hitch-hiking strategy increases the magnitude of T cell activation by >30-fold, compared with standard bolus administration of the antigen alone 173 , 184 .…”
Section: Designing Spatial and Temporal Controlmentioning
confidence: 99%
“…Albumin-binding dyes target draining lymph nodes and thus provide a strategy for the visual identification of sentinel lymph nodes following intratumoural administration 183 . Molecular vaccine cargo can also be designed to ‘hitch-hike’ albumin for the passive targeting of lymph node-resident APCs 173 , 184 . This hitch-hiking strategy increases the magnitude of T cell activation by >30-fold, compared with standard bolus administration of the antigen alone 173 , 184 .…”
Section: Designing Spatial and Temporal Controlmentioning
confidence: 99%
“…57 Instead of albumin hitchhiking, the direct fusion of an antigen peptide to albumin reduces systemic circulation and improved proteolytic stability, as fused proteins traffic to the lymph nodes or are captured by local APCs. 58 With optimized factors, this approach improves vaccine immunogenicity by up to 90-fold and maximizes the responses to viral antigens. 58 SARS-CoV-2 proteins or peptides can be modified with an albumin-binding domain or fused to a carrier protein for lymph node targeting.…”
Section: Route Of Vaccine Administration and Targetingmentioning
confidence: 99%
“…58 With optimized factors, this approach improves vaccine immunogenicity by up to 90-fold and maximizes the responses to viral antigens. 58 SARS-CoV-2 proteins or peptides can be modified with an albumin-binding domain or fused to a carrier protein for lymph node targeting. Elicio Therapeutics repurposed this type of platform and showed an improvement in SARS-CoV-2-specific cellular and humoral immune responses in mice.…”
Section: Route Of Vaccine Administration and Targetingmentioning
confidence: 99%
“…fused tumor‐associated epitopes to minimally immunogenic carrier proteins such as albumin and transthyretin in order to control antigen degradation rates, biodistribution, and PK; they found that immunogenicity was maximized when using carrier proteins with prolonged residence time in local adjuvant‐inflamed draining lymph nodes. [ 124 ] Antigen‐carrier fusions mixed with cyclic di‐GMP, CpG, poly(I:C), or lipo‐CpG adjuvants greatly enhanced the antigen‐specific CD8 + T cell response after immunization. Schudel et al.…”
Section: Perspectives On the Future Of Trm Vaccine Designmentioning
confidence: 99%